1981
DOI: 10.1210/endo-108-2-651
|View full text |Cite
|
Sign up to set email alerts
|

Release of Growth Hormone from Purified Somatotrophs: Use of High K+and the Ionophore A23187 to Elucidate Interrelations among Ca++, Adenosine 3′,5′-Monophosphate, and Somatostatin*

Abstract: Studies were carried out to further define the sites of interaction of Ca++, cAMP, and somatostatin (SRIF) in the mechanisms governing GH release from acutely dispersed purified somatotrophs obtained from rat adenohypophyses. Both high [K+] and the Ca++ ionophore A23187 stimulated the release of GH. The release induced by high [K+] was accompanied by a small but significant transient increase in intracellular cAMP, while A23187 did not alter basal cAMP levels. The augmented release of GH induced by both secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…It is well known that elevated ex ternal level of potassium leads to an increase in the secre tion of anterior pituitary hormones [see ref. 27], This effect has been observed for tumoral [34] and normal pituitary cells [44,48].…”
Section: Effects Of Substances Known To Influence Gh Secretion On Thementioning
confidence: 83%
“…It is well known that elevated ex ternal level of potassium leads to an increase in the secre tion of anterior pituitary hormones [see ref. 27], This effect has been observed for tumoral [34] and normal pituitary cells [44,48].…”
Section: Effects Of Substances Known To Influence Gh Secretion On Thementioning
confidence: 83%
“…However, there appear to exist other mechanisms of somatostatin action for the following reasons: (i) It has been reported in rat GH4Cl cells and in purified rat somatotrophs that somatostatin reduces basal hormone release without a detectable change in cAMP (7,8,31). In addition, basal hormone release is independent of external Ca2l (8,32 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Ca2l is required for GH release evoked by high concentrations of extracellular K+ (8) and GH-releasing factor (4,9). Various anterior pituitary cell lines have b*,n shown to have action potentials that are dependent on Ca2l or Na+ (10).…”
mentioning
confidence: 99%
“…Human pancreatic-tumor growth hormone releasing factor (hGRF) has been demonstrated to be a potent, specific stimu lator o f growth hormone (GH) secretion in vivo and in vitro both in animals and in man [4,5). This peptide meeting certain criteria has been assumed to be similar or identical to hypotha lamic GRF [6][7][8]. The inhibition o f GRF-stimulated GH release by verapamil [9], cobalt [10], or inhibitors o f calcium-binding protein [II] suggests that Ca2* influx into the cell is a necessary Received: September 28, 1988 Accepted after revision: May 9, 1989 step for this release.…”
mentioning
confidence: 99%